Comparison of varios barrel shifter - Abg Muhd Zakaria Abg Abdul Wahed
Barrel shifters are often utilized by embedded digital signal processors and general-purpose processors to manipulate data. This project design alternatives for 16 bit barrel shifters that perform the following function shift left logical. The component for the 16 bit barrel shifter is MSI 74151 IC and 74157 IC. Both of this component will be combine separately to build 16 bit barrel shifter This project are also shows that how does the 16 bit barrel shifter simulate by using Mentor Graphic software. The comparison for both of 16 bit barrel shifter can be determined by the output waveform. From the output waveform, this result will be compare to determine which of this two barrel shifter are efficient. Two different barrel shifter designs are presented and compared in terms of power consumption, frequency, area and delay for a variety of operand sizes. Each component for 16 bit barrel shifter also to be determined and all the result for the 16 bit barrel shifter including for each component will be determined inside this project report for analysis reference.